Ontogenetic niche shifts and resource partitioning in a subarctic piscivorous fish guild - Amundsen, Per-Arne; Bøhn, Thomas; Popova, Olga A.; Staldvik, Frode J.; Reshetnikov, Yuri S.; Kashulin, Nikolay A.; Lukin, Anatoly A. (Springer Nature, 2003)
This is a post-peer-review, pre-copyedit version of an article published in Hydrobiologia . The final authenticated version is available online at http://dx.doi.org/10.1023/A:1025465705717 . The feeding ecology of three piscivorous fish species (perch ( Perca fluviatilis ), pike ( Esox lucius ) and burbot ( Lota lota )), was studied in the subarctic Pasvik watercourse (69 ° N), northern Norway and Russia. All three species primarily occupied the benthic habitats in the watercourse. Perch and burbot exhibited distinct ontogenetic niche shifts in food resource use, perch changing from a dominance of zooplankton to zoobenthos to fish, and burbot from zoobenthos to fish. Fish prey dominated the diet of all the investigated size-classes of pike, but small-sized pike (<20 cm) were not represented in the sample. Fish prey size was positively related to predator size in all three species. Whitefish ( Coregonus lavaretus ) was the dominant prey of pike and large-sized burbot and perch. Nine-spined sticklebacks ( Pungitius pungitius ) was also an important prey and appeared to be a dietary stepping-stone enhancing the transition from invertebrate feeding to consumption of large-sized whitefish prey for all three predators. A cluster analysis separated the different size groups of the three predator species into five functional feeding groups, most of them containing two or all three species. Within these feeding groups, and especially among the piscivorous size-classes, there was a strong and significant interspecific overlap in prey selection, and the dietary similarities between the species were in general much larger than the intraspecific similarities between ontogenetic stages. All three piscivorous species are important top predators in the aquatic food web of the watercourse, and their ontogenetic diet shifts and resource partitioning patterns generate a substantial food web complexity in this subarctic ecosystem.